Sex-specific circRNA–miRNA–mRNA networks in peripheral blood mononuclear cells of patients with idiopathic pulmonary arterial hypertension: a pilot study - Li, Yuan; Sun, Yuanyuan; Huang, Yuxia; Hu, Xiaoyi; Yuan, Ping (Frontiers in Genetics, 2025)
BackgroundIdiopathic pulmonary artery hypertension (IPAH) is a life-threatening condition with obvious sex differences. Recently, the interactions among circRNAs, miRNAs, and mRNAs were found to be significant parts in IPAH. Thus, we want to explore whether RNA networks exist in IPAH via sex differential analyses.Methods and materialsIllumina HiSeq was used to detect differentially expressed (DE) RNAs in peripheral blood mononuclear cells (PBMCs) from six (three male) IPAH patients. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were employed for the exhibition of differential expression levels of circRNAs, miRNAs, and mRNAs. The competing endogenous RNA (ceRNA) networks among circRNAs, miRNAs, and mRNAs were constructed on the basis of the authoritative miRanda and TargetScan databases. Student’s t-test was employed, and p < 0.05 was applied to show significance.ResultsThere were 220 DE circRNAs (106 upregulated and 104 downregulated), 41 DE miRNAs (15 upregulated and 26 downregulated), and 160 mRNAs (65 upregulated and 95 downregulated) in the female group compared with the male group, respectively. Through interaction analyses among circRNAs, miRNAs, and mRNAs, upregulated has-miR-1304-3p might be sponged to hsa-circ-0005723 and hsa-circ-0030276 and downregulated hsa-miR-6859-3p was probably sponged to circ DGKD, to modulate 21 downregulation genes and six upregulation genes, respectively.ConclusionThere were sex differences in a comprehensive circRNA–miRNA–mRNA regulatory network in IPAH.